PERANAN KELUARGA DAN MASYARAKAT DALAM MENDUKUNG INDIVIDU DENGAN DISABILITAS SENSORIK - Janatin Sukmareni; Hastin Trustisari (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to explore the role of families, communities, and the government in supporting people with disabilities, especially in terms of accessibility, self-concept formation, and increasing self-confidence. This article was prepared using the literature review method, because of the idea that existing knowledge is an accumulation of previous knowledge, as well as the idea that we can learn and build from what other researchers have studied from 2013-2024. As for the results of this literature review, namely the role of family and society in supporting individuals with sensory disabilities, it can be concluded that support is not only provided by social support, namely there is educational support, mental support and spiritual support. Apart from that, the importance of internal influence is not only from the family but from outside parties, namely the community. With the right collaboration, we can synergize in providing help and services to people with disabilities.